Analysis of cyclist’s drag on the aero position using numerical simulations and analytical procedures: a case study - Forte, Pedro (2020)
Resistance acting on a cyclist is a major concern among the cycling fraternity. Most of the testing methods require previous training or expensive equipment and time-consuming set-ups. By contrast, analytical procedures are more affordable and numerical simulations are perfect for manipulating and controlling inputs. The aim of this case study was to compare the drag of a cyclist in the aero position as measured using numerical simulation and analytical procedures. METHODS: An elite male cyclist (65 kg in mass and 1.72 m in height) volunteered to take part in this research. The cyclist was wearing his competition gear, helmet and bicycle. A three-dimensional model of the bicycle and cyclist in the aero position was obtained to run the numerical simulations. Computational fluid dynamics (CFD) and a set of analytical procedures were carried out to assess drag, frontal area and drag coefficient, between 1 m/s and 22 m/s, with increments of 1 m/s. The t-test paired samples and linear regression were selected to compare, correlate and assess the methods agreement. RESULTS: No significant differences (t = 2.826; p = 0.275) between CFD and analytical procedures were found. The linear regression showed a very high adjustment for drag (R2 = 0.995; p < 0.001). However, the drag values obtained by the analytical procedures seemed to be overestimated, even though without effect (d = 0.11). CONCLUSIONS: These findings suggest that drag might be assessed using both a set of analytical procedures and CFD